The combined effect of permeation enhancement and proteolysis inhibition on the systemic exposure of orally administrated peptides: Salcaprozate sodium, soybean trypsin inhibitor, and teriparatide study in pigs - Gregory Burshtein; Constantin Itin; Jonathan C.Y. Tang; Hillel Galitzer; William D. Fraser; Phillip Schwartz (Elsevier, 2021)
Oral delivery of peptides and proteins is hindered by their rapid proteolysis in the gastrointestinal tract and their inability to permeate biological membranes. Various drug delivery approaches are being investigated and implemented to overcome these obstacles. In the discussed study conducted in pigs, an investigation was undertaken to assess the effect of combination of a permeation enhancer - salcaprozate sodium, and a proteolysis inhibitor - soybean trypsin inhibitor, on the systemic exposure of the peptide teriparatide, following intraduodenal administration. Results demonstrate that this combination achieves significantly higher Cmax and AUC (~10- and ~20-fold respectively) compared to each of these methodologies on their own. It was thus concluded that an appropriate combination of different technological approaches may considerably contribute to an efficient oral delivery of biological macromolecules.